Answer:
see explanation
Step-by-step explanation:
1
Given
2x² - 16 = 0 ( add 16 to both sides )
2x² = 16 ( divide both sides by 2 )
x² = 8 ( take the square root of both sides )
x = ± [tex]\sqrt{8}[/tex] = ± 2[tex]\sqrt{2}[/tex]
------------------------------------
2
Given
- 5x² + 9 = 0 ( subtract 9 from both sides )
- 5x² = - 9 ( divide both sides by - 5 )
x² = [tex]\frac{9}{5}[/tex] ( take the square root of both sides )
x = ± [tex]\sqrt{\frac{9}{5} }[/tex] = ± [tex]\frac{3}{\sqrt{5} }[/tex]
-----------------------------------------
3
Given
6x² - 15 = 27 ( add 15 to both sides )
6x² = 42 ( divide both sides by 6 )
x² = 7 ( take the square root of both sides )
x = ± [tex]\sqrt{7}[/tex]